Mitigation of intrarenal pressure in retrograde intrarenal surgery with a novel isoprenaline eluting guidewire - John, Jeff (Division of General Surgery, 2025)
Urolithiasis ranks as the third most prevalent condition in urology, with statistical evidence indicating a lifetime risk of 13% in males and 7% in females, alongside a recurrence rate of 50% within a decade. The surgical care of urolithiasis is intricate, with various competing therapeutic techniques available, including retrograde intrarenal surgery (RIRS). Over the years, leading urological associations have progressively broadened the criteria for RIRS in the surgical treatment of urolithiasis. While it offers enhanced stone-free rates relative to shockwave lithotripsy and reduced patient morbidity compared to percutaneous nephrolithotomy, it is not devoid of problems, many of which are associated with intrarenal pressure (IRP). To alleviate the challenges associated with increased IRP, surgeons may utilize diverse approaches to regulate IRP. Pharmacologic therapies in the perioperative period to mitigate IRP have been documented, although none of these strategies have been integrated into clinical practice. This thesis aims to report on the design, safety, and efficacy of an innovative isoprenaline-eluting guidewire (IsoWire), a platform guidewire intended for the administration of topical isoprenaline, a beta-receptor agonist, to the genitourinary system. This is the first study to report the delivery of isoprenaline using a drug-eluting guidewire. This dissertation comprises six chapters. The initial five chapters each have an overview, abstract, introduction, methodology, results, discussion, and conclusion sections. Chapter 1 is a narrative literature review addressing the problems associated with high IRP and outlines techniques to mitigate elevated IRP in RIRS to promote safer endourological practices. To prepare for our investigation on the porcine model, we required a simulation model to precisely outline the procedural procedures. Commercially available models are expensive and not readily accessible. Chapter 2 delineates the design and fabrication of the Frere Intrarenal Surgery Trainer (FiST) bench-top model. This chapter further elucidates its validation through the involvement of individuals with prior competence in the RIRS technique. This high-fidelity, cost-effective, portable, durable, and reusable training model is, to our knowledge, the inaugural published 3D model that integrates all components of RIRS, allowing us to meticulously optimise the procedural stages for our research. The porcine model has frequently been utilized by researchers and urological surgeons for medical advancements. Despite the multiple advantages of this model, the specific anatomical knowledge that qualifies it as the optimal model in urology remains inadequately defined. In Chapter 3, we present the first reported study that precisely delineates pertinent endoscopic and CT-based urological anatomy of female Landrace pigs. The insights acquired from this research were essential for proceeding with the two studies described in Chapters 4 and 5. Furthermore, this unprecedented research will help other researchers use the porcine model to conduct research in endourology with confidence. Chapter 4 delineates the design of the IsoWire and examines the results of the preliminary in vitro release studies. Furthermore, we evaluated IsoWires of three distinct strengths, specifically wires that release 5 μg, 7.5 μg, and 10 μg in the first minute minute, respectively. Our investigation demonstrated that the IsoWire, which released 7.5 μg of isoprenaline within the initial minute, is safe, showing no alterations in mean arterial pressure (MAP), heart rate (HR), or other irregular electrocardiographic (ECG) abnormalities. Moreover, the in vitro release assays demonstrated that the IsoWire released all isoprenaline exponentially within the initial 4 minutes. Chapter 5 delineates the impact of the IsoWire, which dispenses 7.5 μg of isoprenaline within the initial minute, on IRP, the duration of this effect, and its safety in a porcine model. Chapter 6 presents a conclusion and reflection on this thesis, emphasising its original contributions to the field of urology and addressing prospective avenues for future research.